MASALAH DAN KEBIJAKAN SERTIFIKASI PENGELOLAAN HUTAN ALAM PRODUKSI LESTARI: PENERAPAN ADVOCACY COALITION FRAMEWORK - Librianna Arshanti; Hariadi Kartodihardjo; Azis Khan (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2017)
Research about Sustainable Forest Management (SFM) certification is intended to providerecommendation forpolicy implementation in addressingproblems to manage natural forests in Indonesia. Advocacy Coalition Framework (ACF) was employedto understand and explain changes when there are disagreements over the extentof policy regulatory purposes. The objective of this research is to determine the coalition of policy on SFM certification process using ACF by studying the history of related policies, beliefs of the actors and coalition. In addition, the research is alsoto formulate recommendation on the policy direction of SFM certification. This phenomenological research use discourse analysis to ensure the existence of coalition, which in this case areactors, conceptual framework, and the direction ofcoalition based on fixed parameters and external events as indicated in the ACF. The resarch found that in policy decision-making process on SFM certification in Indonesia there are two coalitions that are contradictingininterests. This political research indicates that SFM certification policy assessment tends to comply with applicable government regulations. International timber markets accepted certification of conformity assessment based on the fulfillment of standards and criteria for SFM.